Analisis Metode Camel dan Pearls untuk Menilai Tingkat Kesehatan BPR di Kota Bontang - Abdi Putra Prakoso; F. Defung (Faculty of Economics and Business Mulawarman University, 2017)
This research aims at finding out the differences of health level of BPR in Bontang City by using CAMEL and PEARLS methods in the period of 2014-2015. The methods used in this research were CAMEL and PEARLS methods by determining the health level of a BPR which was classified based on the category of each assessment of the method. The research findings showed that the assessment of health level of BPR in Bontang City by using CAMEL and PEARLS methods had different ways of assessment. In CAMEL method, there was still a BPR which fell into a category which did not meet the standard of health assessment, namely BPR Dhanarta Dwiprima in the period of 2014 to 2015. The result of PEARLS assessment showed all of the BPRs in Bontang City in the period of 2014 to 2015 fell into a healthy category. This difference was caused by the calculation of the health level of BPR using PEARLS, which included indicators of growth ratio, which assessed that BPRs grew from one period to the subsequent period.Keywords: CAMEL, PEARLS, BPR, Health Level of BPR